Inflammatory signature in lung tissues in patients with combined pulmonary fibrosis and emphysema. (3rd April 2019) - Cornwell, William D.; Kim, Cynthia; Lastra, Alejandra C.; Dass, Chandra; Bolla, Sudhir; Wang, He; Zhao, Huaqing; Ramsey, Frederick V.; Marchetti, Nathaniel; Rogers, Thomas J.; Criner, Gerard J.
Abstract: Background: The aetiology and inflammatory profile of combined pulmonary fibrosis and emphysema (CPFE) remain uncertain currently. Objective: We aimed to examine the levels of inflammatory proteins in lung tissue in a cohort of patients with emphysema, interstitial pulmonary fibrosis (IPF), and CPFE. Materials and methods: Explanted lungs were obtained from subjects with emphysema, IPF, CPFE, (or normal subjects), and tissue extracts were prepared. Thirty-four inflammatory proteins were measured in each tissue section. Results: The levels of all 34 proteins were virtually indistinguishable in IPF compared with CPFE tissues, and collectively, the inflammatory profile in the emphysematous tissues were distinct from IPF and CPFE. Moreover, inflammatory protein levels were independent of the severity of the level of diseased tissue. Conclusions: We find that emphysematous lung tissues have a distinct inflammatory profile compared with either IPF or CPFE. However, the inflammatory profile in CPFE lungs is essentially identical to lungs from patients with IPF. These data suggest that distinct inflammatory processes collectively contribute to the disease processes in patients with emphysema, when compared to IPF and CPFE.